Flexural behaviour of glass fiber reinforced polymer (Gfrp) tubes subjected to static load - Syamsir A.; Alhayek A.; Keng A.Y.Y.; Mohamad D.; Rashid M.Z.A.; Norhisham S. (Springer Science and Business Media Deutschland GmbH, 2023)
Glass fibers; Offshore oil well production; Steel beams and girders; Tubes (components); Flexural modulus; Flexural toughness; Four point bending; Glass fiber reinforced polymer; Initial cracks; Mid-span deflection; Static loads; Transmission tower; Fiber reinforced plastics